Physical and Mechanical Properties of Oriented Strand Board Prepared from Acetylated Wood Strands - Apri H Iswanto; Widya Fatriasari; Andi D Yunianti; Ahmad Zailani; Fauzi Febrianto (Masyarakat Peneliti Kayu Indonesia, 2013)
The objectives of this research were to evaluate of the physical and mechanical properties of oriented strand board (OSB) prepared from acetylated wood strands. Strands derived from Acacia mangium wood were immersed in acetic anhydride for 24 h. After that, strands were dried at 60 C to reach moisture content (MC) of 5%. The slenderness and aspect ratios of strands were 100.72±39.42 and 3.05 ± 0.44. Boards size and target density were set at (25x25x0.5) cm3 and 0.7 g cm-3. The strand compositions for face, core, and back layers were 25, 50, and 25%, respectively. Phenol formaldehyde (PF) resin with amount of 8% was used to bind the strands. The results showed that weight percent gain (WPG) of acetylated strands was 4%. Acetylated strands resulted in improvement of dimensional stabilization (water absorption (WA) and thickness swelling (TS) parameters) with anti-shrink efficiency (ASE) value of 19.65%. On the other hand, the modulus of elasticity (MOE), modulus of rupture (MOR) and internal bond (IB) were found to decrease with acetylation treatment. All the physical and mechanical properties of OSB evaluated except IB parameter fulfilled the requirements of JIS A 5908-2003 standard.Key words: acetylated, anti-shrink efficiency, dimensional stability, oriented strand board